Presencia de quistes en Tritrichomonas muris - Chinchilla, M.; Portilla, E.; Guerrero, O. M.; Marín, R. (Revista de Biología Tropical, 1987)
Cysts o f Tritrichomonas muris are reported. The morphology of this evolutive stage is described under light and electro n microscopy. The biologic and epidemiologic importance of this finding is discussed.